2015
DOI: 10.3168/jds.2014-8528
|View full text |Cite
|
Sign up to set email alerts
|

Fat and starch as additive risk factors for milk fat depression in dairy diets containing corn dried distillers grains with solubles

Abstract: Two experiments were conducted to evaluate the additive effects of starch and fat as risk factors associated with milk fat depression in dairy diets containing corn dried distillers grains with solubles. In experiment 1, 4 multiparous ruminally cannulated Holstein cows, averaging 114±14 d in milk and 662±52 kg of body weight, were randomly assigned to 4 treatments in a 4×4 Latin square to determine the effect of these risk factors on rumen fermentation and milk fatty acid profile. In each 21-d period, cows wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 38 publications
5
21
2
Order By: Relevance
“…Milk 16C FA did not differ by day or treatment throughout the duration of this study. Alterations in de novo and preformed FA are characteristics commonly reported in studies investigating MFD, with de novo FA decreasing during MFD and the preformed FA increasing significantly (Ramirez Ramirez et al, 2015;Rico et al, 2015a). These results suggest that StK d represents a factor that may inhibit full recovery from MFD.…”
Section: Dmi and Milk Composition And Yieldsupporting
confidence: 56%
See 1 more Smart Citation
“…Milk 16C FA did not differ by day or treatment throughout the duration of this study. Alterations in de novo and preformed FA are characteristics commonly reported in studies investigating MFD, with de novo FA decreasing during MFD and the preformed FA increasing significantly (Ramirez Ramirez et al, 2015;Rico et al, 2015a). These results suggest that StK d represents a factor that may inhibit full recovery from MFD.…”
Section: Dmi and Milk Composition And Yieldsupporting
confidence: 56%
“…Similarly, high-starch diets increase ruminal propionate production and flux to the liver, stimulating hepatic oxidation and generation of ATP, which can also reduce DMI (Bradford and Allen, 2005;Albornoz and Allen, 2018). Ramirez Ramirez et al (2015) and Harvatine and Allen (2006a) reported reductions in DMI with high PUFA intake. Harvatine et al (2009b) suggested that under MFD conditions as a result of the reduction in milk energy output, energy can be partitioned toward body reserve replenishment.…”
Section: Induction Of Mfdmentioning
confidence: 99%
“…To provide sufficient energy for high-yielding dairy ruminants, they are typically fed starch-enriched diets. However, starch-enriched diets are known to increase the risk of milk fat depression (MFD) in dairy cows [1][2][3]. MFD is a multifactorial disorder characterized by sustained reduction in milk fat synthesis, which can reduce milk fat production and milk quality, induce potentially adverse effects on animal health and bring about important economic losses [4].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, feeding of unsaturated fatty acids to ruminants has long been known to induce milk fat depression Ensor et al, 1959;Maynard et al, 1936;Moore et al, 1945;Ramirez Ramirez et al, 2015). Both the 10 and 20% DDGS treatment diets had significantly less SFA, more PUFA, and more unsaturated fatty acids (UFA) ( Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Feeds containing high concentrations of unsaturated fatty acids (i.e., corn oil in distillers grains) negatively influences production parameters of lactating dairy cattle through inhibition of ruminal fiber digestion Ensor et al, 1959;Maynard et al, 1936;Moore et al, 1945;Ramirez Ramirez et al, 2015;Zinn et al, 1989) and inhibition of de novo lipogenesis in the mammary gland, particularly through the action of trans-10 cis-12 conjugated linoleic acid . Additionally, diets with a concentration of fat over 5% can negatively influence milk production, regardless of degree of unsaturation (Zinn et al, 1989).…”
Section: Overall Summary and Justification Of Researchmentioning
confidence: 99%